A Study on Training factors and its effect that influence employee performance in Sarawak Energy Berhad / Adeline Kumong - Kumong, Adeline (2016)
In Malaysia so many enterprise implement various training program to enhance their employees by working performance. But as overall view, the training environment still exist shortages in enterprise today, for instance, lack of knowledge of training, resources, trainer etc. Employee training has been a matter of concern and attention by many business fields nowadays. Organizations realize that employee training is an essential element to increase efficiency of job performance and keep their business running, as competition are getting more intense.